2015
DOI: 10.3109/14647273.2015.1071500
|View full text |Cite
|
Sign up to set email alerts
|

Rescue hCG to treat empty follicle syndrome after the use of a GnRH agonist as oocyte maturation trigger: First report on fresh embryo transfer and clinical pregnancy

Abstract: We present a case series and literature review on the use of rescue human chorionic gonadotropin (hCG) in cases of empty follicle syndrome (EFS) after a gonadotropin-releasing hormone agonist (GnRHa) trigger. EFS was diagnosed after failure to collect any oocytes from one ovary. In such cases, a single dose of hCG was administered and the oocyte retrieval was repeated 36 h later. The main outcome measures were the number of mature oocytes (M2) and embryos (2PN), incidence of hospitalisation for severe ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Interestingly, Christopoulos et al (17) reported six EFS patients after GnRHa trigger, having a mean age of 32.6 years, a mean antral follicle count of 27 and a mean basal FSH level of 4.4 UI/l, rather far from the LH value defining the hypogonadotropic hypogonadal patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Christopoulos et al (17) reported six EFS patients after GnRHa trigger, having a mean age of 32.6 years, a mean antral follicle count of 27 and a mean basal FSH level of 4.4 UI/l, rather far from the LH value defining the hypogonadotropic hypogonadal patient.…”
Section: Discussionmentioning
confidence: 99%
“…This prompted many clinics to recommend donors to have a serum measurement in the fertility clinic 12 h after the GnRHa trigger. However, urine LH measurement performed at home should predict the correct response to the GnRHa trigger, and if needed, the administration of a rescue bolus of hCG (re-trigger) and re-scheduling could avoid EFS or a low follicle mature oocyte ratio (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, EFS has also been reported in young patients with normal or high ovarian reserve. Christopoulos et al (2015) reported six patients with EFS having a mean age of 32.6 years, mean basal FSH level of 4.4 Ui/l and mean antral follicle count of 27. These cases, however, were observed after GnRH-agonist trigger, because of a high risk of ovarian hyperstimulation syndrome (more than 18 follicles >11 mm plus serum oestradiol around 5,000 pg/ml).…”
Section: Genuine Efsmentioning
confidence: 99%
“…Nevertheless, EFS may occur even after GnRH-agonist trigger and the consequent endogenous LH peak (Asada et al, 2013;Christopoulos et al, 2015). In recent years, GnRH-agonist trigger has been used more frequently in the case of high responders who bear a high risk of developing severe OHSS (Banker and Garcia-Velasco, 2015;Engmann and Benadiva, 2012;Humaidan et al, 2013), as its best characteristic is the much lower risk of stimulating the onset of the syndrome in comparison to HCG.…”
Section: Genuine Efsmentioning
confidence: 99%
See 1 more Smart Citation